A new concept to design inductors with low conducted and radiated emission noises - Zare, Firuz (2016)
© 2016 IEEE and EPE Association. This paper presents a new configuration of inductor utilized in modern power electronics systems with high switching frequency. The main advantage of the proposed inductor is to suppress high frequency conducted and radiated emission noises. Several high frequency analysis and measurement have been carried out to verify the proposed concept.